Pembinaan Pemusik Gereja dan Pemandu Lagu di GMIT Jemaat Betel Oefafi - Rudi Fanggidae; Glorius Keo; Meyrlin Saefatu (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The Oefafi Bethel Church is the target of Community Service activities. Based on the initial survey, problems were found, namely the inconsistency of the use of style in the music genre, the use of inappropriate tempos, intros and endings, not being able to distinguish between classical and contemporary ways of singing, not mastering punctuation marks and the accuracy of notes in singing are some of the obstacles that we often encounter in church music services in rural areas and even in urban areas which are often carried out by church musicians and guides song. The methods used in this activity are lectures, discussions, questions and answers, and demonstrations. This activity was attended by 11 participants. With this activity, musicians and song guides can sound and sing the congregation's songs properly and correctly according to the genre, intro, tempo, using song punctuation, and song notation.